Demonstration Of Complementary Feeding (Mp-Asi) With Increased Knowledge In Mothers Of Toddlers As A Form Of Stunting Prevention In Hamlet II Pekik Nyaring Village Central Bengkulu - Andini, Delta; Susilawati , Diah Putri; Cahaya.M, Anggun; Nuvriyanti , Iza; Hilinti , Yatri; Murwati, Murwati (Jurnal Pengabdian Mandiri, 2024)
In 2017, around 150.8 million children under five (22.2%) in the world were stunted. Based on Nutrition Status Monitoring Data (PSG), over the last three years the incidence of short toddlers has the highest prevalence compared to other nutritional problems such as undernutrition and overnutrition. This is supported by data from the World Health Organization (WHO) which states that Indonesia is included in the third country with the highest stunting prevalence in the Southeast Asian region. The prevalence of stunting rates in toddlers in 2000 was 27.5%. In 2016, it increased by 29.6% (Ministry of Health, 2018).The purpose of this study is to determine the Distribution of Knowledge Frequency before and after being given complementary food demonstration activities (MP-ASI) by increasing knowledge in mothers under five as a form of stunting prevention in hamlet II, Pekik Nyaring village, Central Bengkulu. The method used in this study is through 2 activities, namely lectures and questions and answers. Results and Discussion in this KKN activity with the title "Demonstration of complementary foods for breast milk (MP-ASI) with increased knowledge in mothers under five as a form of stunting prevention in hamlet II of Pekik Nyaring village, Central Bengkulu" Based on the analysis of the results of the questionnaire that has been given to the respondents, the results of the distribution of knowledge frequency between pre test and post-test show that at the time of the pretest most of the respondents had a sufficient level of knowledge, namely as many as 12 people (80%). After the posttest, 12 of them (80%) had a good level of knowledge. Suggestion: The results of this demonstration activity are expected to provide information to further develop and add scientific insights, especially about complementary foods for breast milk (MP-ASI) as a form of stunting prevention.